Implementation of ICT-Based Quiz Design Training in Improving the Pedagogic Competence of Madrasah Ibtidaiyah Teachers in Sei Tulang Raso District - Wandini, Rora Rizky; Daulay, Sholihatul Hamidah (Edumaspul: Jurnal Pendidikan, 2024)
Information and Communication Technology (ICT)-based quiz design training is important in improving the pedagogical competence of Madrasah Ibtidaiyah teachers in Sei Tulang Raso District. In the context of modern education, the use of ICT as a learning tool has a very significant role. This study aims to explore the impact of ICT-based quiz design training on the pedagogical ability of Madrasah Ibtidaiyah teachers. This study used quantitative and qualitative approaches to collect data from teachers who attended this training. The results showed that ICT-based quiz design training was effective in improving teachers' pedagogic skills. Teachers who attended this training experienced an increase in designing engaging and interactive quizzes using technology. They also gained a better understanding of the integration of ICT in daily learning, which in turn improved the quality of teaching in Madrasah Ibtidaiyah. This research makes an important contribution to our understanding of the importance of ICT training in the context of religious education, particularly in Madrasah Ibtidaiyah. The practical implication of this research is the development of better training strategies to support teachers in the face of 21st century learning demands. In addition, the results of this study also provide a basis for more effective and relevant education policies in the future.